Problematizing Canadian exceptionalism - Laura J. Kwak (Oñati Socio-Legal Series)
The myth that Canada has resisted the “West’s populist wave” persists despite evidence that demonstrates otherwise. This article traces how the assumption that Canada has avoided the rise of right-wing populism and white nationalism is tethered to the fiction that Canada has been a raceless society. After briefly reviewing the myth of racelessness and the history of right-populism in Canada, the article explores how the Reform Party of Canada conceptualized “the people” in racialized terms. This article examines how the Conservative Party of Canada’s appeals to symbolic “diversity” and denial of systemic oppression have enabled more overt forms of racism. By examining the recent rise of hate crimes, this article makes the case that a direct link can be traced between the Conservative government’s seemingly neutral discourses about the preservation of Canadian “heritage” and “common values” and the re-emergence of right-wing populism and the re-emboldening of white nationalism in Canada.